The Effect of Endorphine Massage to Reduce Pain During the First Stage of Labor: Evidence Based Case Report - Alfiya Fauzani, Marsya; Widiawati, Ida; Sriwenda, Djudju (Universitas Ibn Khaldun Bogor, 2024)
Background: Labor is a physiological process that every pregnant woman will experience in her reproductive cycle. The changes that occur in the body to prepare for childbirth often cause pain in the mother. Physical changes will also affect the emotional and psychological condition of the birthing mother, such as stress and anxiety. One non-pharmacological methods to reduce pain during labor is endorphine massage. This massage aims to make the mother comfortable and calm by helping to release endorphin hormones which play a role in increased analgesic response during labor. Endorphine massage is performed by giving a light touch to the back area to help release the hormones endorphins and oxytocin during the first stage of labor. Purpose: To determine the effect of endorphin massage on reducing pain in the first stage of labor. Method: Evidence based case report (EBCR) by searching several articles via Google Scholar and Portal Garuda. Result: There was a decrease in pain intensity of first stage of labor from severe to moderate pain after being given endorphins massage for 5 minutes every hour. Conclusion: The results of the case report show that endorphin massage can reduce pain in the first stage of labor.